Comparing Perceived Pain Impact Between Younger and Older Adults With High Impact Chronic Pain: A Cross-Sectional Qualitative and Quantitative Survey - You, Dokyoung S.; Ziadni, Maisa S.; Hettie, Gabrielle; Darnall, Beth D.; Cook, Karon F.; Von Korff, Michael R.; Mackey, Sean C. (Frontiers in Pain Research, 2022)
High impact chronic pain (HICP) is a recently-proposed concept for treatment stratifying patients with chronic pain and monitoring their progress. The goal is to reduce the impact of chronic pain on the individual, their family, and society. The U.S. National Pain Strategy defined HICP as chronic pain associated with substantial restrictions on participation in work, social, and self-care activities for at least 6 months. To understand the meaning and characteristics of HICP from the younger (< 65 years old) and older adults (≥ 65 years old) with chronic pain, our current study examined patients’ perceived pain impact between the two age groups. We also characterize the degree of pain impact, assessed with the PROMIS-pain interference, between adults and older adults with HICP. We recruited patients at a tertiary pain clinic. The survey included open-ended questions about pain impact, the GCPS-R to identify patients meeting criteria for HICP, and the Patient-Reported Outcomes Measurement Information System (PROMIS®) 8-item pain interference (PI) short form (v.8a). A total of 55 younger adults (65.5% female, 72.7% HICP, mean age = 55.0 with SD of 16.2) and 28 older adults (53.6% female, 64.3% HICP, mean age = 72.6 with SD of 5.4) with chronic pain participated in this study. In response to an open-ended question in which participants were asked to list areas of major impact pain, those with HICP in the younger group most commonly listed work, social activity, and basic physical activity (e.g., walking, standing); for those in the older group, the most common were basic physical activity, instrumental activity of daily living (e.g., housework, grocery shopping), and participating in social or fun activity for older adults with HICP. A 2x2 ANOVA was conducted using age (younger adults vs older adults) and HICP classification (HICP vs No HICP). A statistically significant difference was found in the PROMIS-PI T-scores by HICP status (HICP: M=58.4, SD=6.3; No HICP: M=67.8, SD=6.3), but not by age groups with HICP. In conclusion, perceived pain impacts were qualitatively, but not quantitatively different between younger and older adults with HICP. We discuss limitations and offer recommendations for future research.